sinergitas hubungan sinergitas hubungan antara dunia usaha media,pemerintah dan LSM: sinergitas hubungan antara dunia usaha media, pemerintah dan LSM - Putri Putri; Ilham Tahier; Rani Rani; Miranti Miranti; Anghrina Ananta Sudirman; Claudya Amal Utami (Universitas Slamet Riyadi, 2024)
This study aims to analyze the synergy of relationships between the media industry, the government and NGOs. Synergy According to the great Indonesian dictionary,